2017
DOI: 10.1111/add.13872
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on Blowet al.(2017): Leveraging technology may boost the effectiveness and adoption of interventions for drug use in emergency departments

Abstract: The effect of brief interventions for drug use can depend upon the type and severity of substance use, as well as psychosocial stability and other variables. Innovative technology, such as the computer delivered or assisted approaches tested by Blow et al., should be used to support implementation of brief interventions by maintaining simplicity and enhancing efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Given the frequent overlap of homelessness and substance use among ED patients, surprisingly little attention has been paid to housing status in prior ED-based SBIRT (screening, brief intervention, and referral to treatment) and other substance use interventions. Overall, ED-based SBIRT programs have shown modest success for alcohol and mixed results for drug use (McCormack, 2017). No prior research has examined how housing status may affect the success of SBIRT or other ED-based substance use interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the frequent overlap of homelessness and substance use among ED patients, surprisingly little attention has been paid to housing status in prior ED-based SBIRT (screening, brief intervention, and referral to treatment) and other substance use interventions. Overall, ED-based SBIRT programs have shown modest success for alcohol and mixed results for drug use (McCormack, 2017). No prior research has examined how housing status may affect the success of SBIRT or other ED-based substance use interventions.…”
Section: Discussionmentioning
confidence: 99%
“…D' Onofrio et al (2015) found that brief intervention in the ED for patients with opioid use disorder did not improve rates of treatment attendance at 30 days compared to referral alone. Even if in-person motivational interventions were found to be effective, time, personnel and training barriers preclude implementation in most EDs (McCormack, 2017).…”
Section: Prior Behavioral Interventions For Sud Treatment Linkagementioning
confidence: 99%
“…• It reduces cost through decreasing expensive clinician time (McCormack, 2017), expands revenue by increasing the number of clients receiving services, and maximizes billing by accurately documenting SBIRT in the electronic health record.…”
Section: Why Should I Care? the Benefits Of Technology-enabled Sbirtmentioning
confidence: 99%